SCREENING OF BIOLOGICALLY ACTIVE COMPOUNDS FROM Megacarpaea polyandra BENTH ROOT: A TRADITIONAL MEDICINAL PLANT OF THE HIMALAYAS - Imtiaz Bashir; Shabir Ijaz; Raheem Shahzad; Abid Khan; Najeeb Ullah; Majid Alhomrani; Walaa F Alsanie; Abdulhakeem S Alamri (Journal of the Chilean Chemical Society, 2025)
Megacarpaea polyandra Benth belonging to the Brassicaceae family is a medicinal plant found in alpine meadows and open forests between 3000-4300 meters in E. Asia-Himalayas. Traditionally, the plant has been used to treat various illnesses, including fever, diarrhea, asthma, and gastrointestinal problems. The root is used for relieving stomach aches, pneumonia, and fever. This study aimed to apply gas chromatography and mass spectroscopy analysis (GC-MS) to analyze the phytochemical components present in M. polyandra root. In the current study, this plant has been worked for the first time in terms of chemicals. The ethanolic root extract of the plant derived 207 phytochemicals. Of them, 47 were recorded as highly bioactive, among the recorded bioactive chemicals some compounds, viz furaneol;  catechol; 2H-Imidazole-2-thione, 1,3-dihydro-1-methyl; undecanoic acid; n-Hexadecanoic acid;  heptadecanoic acid; oleic Acid; Pyridine-4-carboxylic acid, 2-amino-3-cyano-5,6-dimethyl-, ethyl;  .beta.-Sitosterol and pilocarpine  have several biological properties. This includes antioxidant, anti-microbial, anti-cancer, anti-inflammatory, cure nervous system disorders, blood pressure regulators, anti-diabetic, and anti-inflammatory qualities.  The chemicals were identified by interpreting the mass spectra and comparing their peak area and retention time with those in the literature. According to the current study's findings and conclusions, plant roots may be a useful resource for the development of herbal drugs due to the presence of various bioactive molecules responsible for curing the above-mentioned illnesses. The use of plant roots to treat a variety of illnesses with fewer adverse effects is justified by the existence of bioactive chemicals, which also suggests that the plant is of medicinal relevance. However, further research is required to fully understand its toxicity profile and bioactivity and clarify its vast potential for pharmacological application.